Závěsný cyklonosič pro autobusovou dopravu - Svoboda, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Tato bakalářská práce se zabývá návrhem konstrukce univerzálního cyklonosiče na různé druhy autobusů. Cílem bylo vyrobit jednoduchou, lehkou, bezpečnou, cenově přístupnou konstrukci cyklonosiče se snadným zavěšením kol, ale také přístupem do prostoru motoru autobusu.

This bachelor´s thesis describes the construction of universal the rack for bicycles to different types of buses. The aim was to produce a simple, lightweight, safe, affordable, accessible design of the rack for bicycles with easy the suspension, but also with the access to the engine compartment of the bus.
Suspended bicycle carrier for buses
Keywords: Konstrukce závěsného cyklonosiče; univerzální konstrukce; základní profily; vliv vibrací na rám; Design of hanging bike carrier; universal design; basic profiles; effect of vibrations to the frame